The emotional politics of limerence in romantic comedy films - Moss-Wellington, Wyatt (Amsterdam University Press, 2019)
‘Limerence’ describes the intensity of emotions often felt during the pair-forming stage of a romantic relationship, a period that is also the primary focus of many romantic comedy films. This article asks how filmmakers have used depictions of limerence to highlight spaces in which its potential for both disruption and loving care could be brought to political spheres. I look at a series of millennial romantic comedies that express emotional upheaval, vulnerability, and openness to change as qualities of relevance to both a romantic and political selfhood. These ‘political romcoms’ reveal a range of dynamic relations between notions of character competence, moral fibre, personality and deservedness, and invite investigation of complex emotions that modify a more generalised positive affect associated with romantic comedy cinema: humiliation as a comic device and the existential fear of rejection.